Rearrangement of allyl phenyl ether over Al-MCM-41 - Mathew, Nevin T.; Khaire, S.; Mayadevi, S.; Jha, Ratnesh Kumar; Sivasanker, S. (Journal of Catalysis, 2005)
Claisen rearrangement of allyl phenyl ether to o-allylphenol and a dihydrobenzofuran derivative was investigated over MCM-41 with different Si/Al ratios. Higher aluminum content, higher reaction temperatures, and longer run duration favor the formation of the ring compound 2,3-dihydro-2-methyl benzofuran. There is a close relationship between acidity and conversion, which suggests that the reaction occurs inside the large pores of MCM-41. The influence of temperature and catalyst Si/Al ratio on the reaction are examined by kinetic analysis, under the assumption of a first-order consecutive reaction. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: Al-MCM-41; allyl phenyl ether; Claisen rearrangement; Mesoporous material; molecular rearrangement; Solid acids

Reactions in supercritical carbon dioxide - Mayadevi, S. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Use of conventional organic solvents often leads to the formation of hazardous waste, the disposal of which is a matter of environmental concern. Carbon dioxide is considered to be a green reaction medium and a good replacement for conventional organic solvents as it is benign and leads to elimination/reduction of hazardous wastes. Use of CO2 at near/above critical conditions has several additional advantages as the reactions can be pressure-tuned to eliminate transport resistance, increase solvent power and heat capacity. Hence, there has been considerable interest in the use of supercritical carbon dioxide as either a replacement of conventional organic solvent or as a co-solvent in reactions. Herein, recent developmenst in this area during the last decade is reviewed, specifically in gas-liquid (organic hydrogenation, hydroformylation and oxidation) and liquid-liquid (carbon-carbon coupling, alkylation, acetylation, esterification) reactions.
Keywords: Alkylation; Carbon dioxide; Hydroformylation; Hydrogenation; Oxidation; Supercritical carbon dioxide